Inhibitory NKG2A+ and absent activating NKG2C+ NK cell responses are associated with the development of EBV+ lymphomas - Vietzen, Hannes; Staber, Philipp B.; Berger, Sarah M.; Furlano, Philippe L.; Kühner, Laura M.; Lubowitzki, Simone; Pichler, Alexander; Strassl, Robert; Cornelissen, Jan J.; Puchhammer-Stöckl, Elisabeth (Frontiers in Immunology, 2023)
Epstein-Barr virus (EBV) is a ubiquitous herpesvirus, which infects over 90% of the adult human population worldwide. After primary infections, EBV is recurrently reactivating in most adult individuals. It is, however, unclear, why these EBV reactivations progress to EBV+ Hodgkin (EBV+HL) or non-Hodgkin lymphomas (EBV+nHL) only in a minority of EBV-infected individuals. The EBV LMP-1 protein encodes for a highly polymorphic peptide, which upregulates the immunomodulatory HLA-E in EBV-infected cells, thereby stimulating the inhibitory NKG2A-, but also the activating NKG2C-receptor on natural killer (NK) cells. Using a genetic-association approach and functional NK cell analyses, we now investigated, whether these HLA-E-restricted immune responses impact the development of EBV+HL and EBV+nHL. Therefore, we recruited a study cohort of 63 EBV+HL and EBV+nHL patients and 192 controls with confirmed EBV reactivations, but without lymphomas. Here, we demonstrate that in EBV+ lymphoma patients exclusively the high-affine LMP-1 GGDPHLPTL peptide variant-encoding EBV-strains reactivate. In EBV+HL and EBV+nHL patients, the high-expressing HLA-E*0103/0103 genetic variant was significantly overrepresented. Combined, the LMP-1 GGDPHLPTL and HLA-E*0103/0103 variants efficiently inhibited NKG2A+ NK cells, thereby facilitating the in vitro spread of EBV-infected tumor cells. In addition, EBV+HL and EBV+nHL patients, showed impaired pro-inflammatory NKG2C+ NK cell responses, which accelerated the in vitro EBV-infected tumor cells spread. In contrast, the blocking of NKG2A by monoclonal antibodies (Monalizumab) resulted in efficient control of EBV-infected tumor cell growth, especially by NKG2A+NKG2C+ NK cells. Thus, the HLA-E/LMP-1/NKG2A pathway and individual NKG2C+ NK cell responses are associated with the progression toward EBV+ lymphomas.